Cyanobacteria in aquatic systems of the Americas - Bonilla, Sylvia (2019)
The Americas are one of the world's major natural freshwater reserves, characterized by diverse climatesand heterogeneous ecosystem types. In these sites, eutrophication and climate change are drivers for the loss of water quality, trigging the growth of potentially toxic planktonic cyanobacteria. Blooms of these organisms threaten the use of water for many different purposes, often resulting in negative local economic impactsin developing countries. Cyanobacteria are aheterogeneous group of organisms, and major evolutionary differences between taxonomic orders results in diverse physiological and morphological traits and environmental preferences. Studies with a large geographical perspective allow for comparisonsof cyanobacteria at different taxonomical levels and across ecoclimatic regions. In this study, we investigate the distribution of planktonic cyanobacteria in lakes around the Americas with a gradient of over 135 degrees of latitude, from Tierra del Fuego, 54°51'S (Argentina) to Ellesmere Island, 82°54'N (Canada). We performed a survey using unpublished and published data from 1300 lakes, including limnological and environmental variables, ecoregion information, phytoplankton and detailed datafor more than 150,000cyanobacterial populations, with researchers from 13 institutions and eightcountries.We present preliminary results seeking to identify the main patterns in latitudinal distribution of total cyanobacteria and their major taxonomicorders in relation to trophic state, morphometric and climatic variables. Our results will have important implications for the health of aquatic ecosystems and the human populations that rely on them.